The Effect of Crude Jackfruit (Artocarpus heterophyllus) Leaf Extract on Pseudomonas fluorescens Bacteria In Vitro - Nilakandhi, Tania; Laily, Anggita Noer; Hidayati, Desy Amalia; Sumiana, I Kadek; Riyadi, Farid Mukhtar; Fauzi, Arini Resti (Journal of Fish Health, 2025)
Cultivation activities often experience obstacles due to bacterial disease attacks, one of which is caused by P. fluorescens bacteria. Commercial treatment efforts include the use of antibiotics, but this can cause bacterial resistance. Therefore, an alternative treatment that is more environmentally friendly but can still be used as medicine is needed, namely the use of natural ingredients such as jackfruit (A. heterophyllus) leaves. This study aims to determine the effect of crude jackfruit (A. heterophyllus) leaf extract on P. fluorescens bacteria in vitro. This study used an experimental method with a Completely Randomized Design (CRD) consisting of 5 treatments, 2 controls, and 3 replications. The control treatment consisted of a positive control (Tetracycline 30 ppm), and a negative control (only using disc paper), as well as 5 different extract dose treatments, namely treatment A (60 ppm), treatment B (120 ppm), treatment C (180 ppm), treatment D (240 ppm) and treatment E (300 ppm). The results of the study showed that the use of crude jackfruit (A. heterophyllus) leaf extract affected P. fluorescens bacteria. The relationship between the use of crude jackfruit (A. heterophyllus) leaf extract with different doses and the resulting inhibition zone showed a quadratic regression pattern with the equation y = -0.0001x2 + 0.05x + 6.327.